Bioinspired Fiber-Optic Vector Flow Sensor based on Enhanced Vernier Effect for marine sensing - Wang, Yujia; Fu, Xianping (IEEE access, 2024)
As the flow rate can vary significantly among diverse oceanic regions, it is imperative to design the flow sensors in accordance with the intended measurement flow range or resolution. In this paper, we propose a bio-inspired optical flow sensor prototype based on the enhanced Vernier effect, which allows to design sensor materials and parameters depending on desired measuring range and resolution. The sensor model takes inspiration from the hair cells of fish, utilizing embedded Fabry-Perot interferometers besides cupula as the enhanced Vernier effect sensory element to boost the deflection signal of the protruding cupula caused by water flow. The optical spectra of the Vernier signal, under varying FP cavity parameters, are presented to exhibit the characteristics of the sensing element. This can assist in guiding the selection of sensor parameters. This article also highlights the directional sensing capabilities of the vector flow sensor. Furthermore, four different models, each with their designated materials and parameters, have been presented. These models showcase the ability to measure velocities on either directions of different ranges, from small to large, within specific ranges of 0 m/s - 0.05 m/s and 0 m/s - 0.9 m/s. The proposed sensor can be utilized as a model for marine vector flow sensing, which can be designed according to the desired flow range and sensitivity.